Somatotypes of East-Zone Indian Inter-University Kho-Kho Players - Phukon, Ankur Jyoti; Farooque, Sm; Dhar, Krishnendu (Physical Education Theory and Methodology, 2023)
Background. Somatotyping in modern sports can be an important factor to be considered. Different studies have already taken the initial step to identify the sport-specific somatotypes for different games and sports. In contrast with the Kho-Kho game, some attempts have been made to identify somatotypes specific for these games. But there are only few studies that have been conducted, and various areas are still waiting to be explored. Study purpose. The present study aimed to identify the specific somatotypes of the kho-kho players. Additionally, this study also made an attempt to explore the important somatic traits that influence the somatotypes of the Kho-Kho players. Materials and methods. A total number of 74 players from six Kho-Kho teams that participated in East Zone Inter-University Tournament were purposively selected for the study. The anthropometric data collection was done according to the standard procedures given by ISAK (International Society for Advancement of Kinanthropometry). The statistical analysis was done by using MS Excel (2021) and SPSS’23. Results. The results of the study showed that most of the Kho-Kho players (90.6%) were possessing ectomorphic and mesomorphic dominant traits. There was also a significant difference found in ectomorphic and mesomorphic traits among the players possessing mesomorphic-ectomorph (p<0.05), ectomorphic-mesomorph (p<0.05) and ectomorph-mesomorph (p<0.05) somatotypes. Furthermore, the discriminant analysis also highlighted that attributes of ectomorphic traits (Discriminant coefficient = 1.168) and mesomorphic traits (Discriminant coefficient = 0.812) were important somatic traits for the Kho-Kho players. Overall, 88.6% of the original cases have been correctly represented by the discriminant analysis. Conclusions. The present study showed that Kho-Kho players for the most part possess the ectomorphic and mesomorphic dominant somatotypes. Furthermore, based on the study results, it can be also concluded that somatic attributes in the similar body types also play important role to determine players’ performance level.